2007
DOI: 10.1590/s0102-67202007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico de trauma abdominal submetido à laparotomia exploradora

Abstract: InTRODUÇÃOSegundo as concepções médico-sanitaristas, o trauma caracteriza-se pela existência de lesão, ferida, dano ou prejuízo produzidos no organismo e na mente. Seus condicionantes e causas são variados e predominantemente de origem externas, ainda que a expressão sintomática e as manifestações clínicas sejam influenciadas por mecanismos de funcionamento interno ao próprio organismo. Sabese que as suas conseqüências mórbidas não são totalmente previsíveis sendo, assim, limitadas as possibilidades de control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 5 publications
4
6
0
10
Order By: Relevance
“…Although in the cases of IML-BH the penetrating trauma due to gunshots represented a percentage greater than that found in the Florianópolis study (89.3% and 75.6%, respectively) 19 , that study also evaluated patients who survived the trauma (89.8% of those who underwent surgery), which may justify this difference 19 .…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Although in the cases of IML-BH the penetrating trauma due to gunshots represented a percentage greater than that found in the Florianópolis study (89.3% and 75.6%, respectively) 19 , that study also evaluated patients who survived the trauma (89.8% of those who underwent surgery), which may justify this difference 19 .…”
Section: Discussionmentioning
confidence: 83%
“…However, in the IML-BH sample, as well as in the data from the Florianópolis study 19 , it was observed that gunshot wounds were more frequent than stabbing wounds. The IML-BH greater proportion of gunshot wounds among the penetrating traumas is justified by the fact that abdominal injuries gunshots represent up to 90% of the mortality in penetrating AT 13 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations